Penggunaan Model Pembelajaran Jigsaw Dan Problem Solving Terhadap Motivasi Dan Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi - Sau, Tenri; Ekawarna, Ekawarna; Syuhada, Siti; Mayasari, Mayasari (Business and Accounting Education Journal, 2023)
This study aims to find out, see and analyze the use of the Jigsaw Learning Model and Problem Solving on Student Motivation and Outcomes in economics subjects. The method used in this study is a quantitative method with a quasi-experimental research approach. The population in this study were 95 students of SMA Negeri 6 Tanjung Jabung Timur and a sample of 63 people using a purposive sampling technique. Data analysis used the inferential statistical analysis method and Ancova. The results of the hypothesis testing analysis show that (1) there is a significant influence of the jigsaw learning model on students' learning motivation with a significance value of 0.001 <0.05. (2) there is a significant influence of the jigsaw learning model on student learning outcomes with a significance value of 0.002 <0.05. (3) there is a significant effect of the problem solving learning model on student motivation with a significance value of 0.000 <0.05. (4) there is a significant effect of the problem solving learning model on student learning outcomes with a significance value of 0.002 <0.05.